2007
DOI: 10.1111/j.1365-2362.2007.01769.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental determinants of the PON‐1 phenotype

Abstract: PON-1 Q192R, C-107T and L55M genotype, alcohol consumption, smoking and HDL levels are determinants of serum PON-1 phenotype. The contributions of the genetic markers to the PON-1 phenotype are stronger than the contributions of the lifestyle determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 26 publications
10
37
1
2
Order By: Relevance
“…PON1 activity was the highest in CC and the lowest in TT genotype (CC>CT>TT) of promoter -108C>T polymorphism. The same results were obtained by other authors in population-based studies [3,28]. It was suggested that -108 polymorphism is localized within a probable binding site for Sp1, a ubiquitous transcription factor common in TATA-less genes such as PON1 [3].…”
Section: Discussionsupporting
confidence: 84%
“…PON1 activity was the highest in CC and the lowest in TT genotype (CC>CT>TT) of promoter -108C>T polymorphism. The same results were obtained by other authors in population-based studies [3,28]. It was suggested that -108 polymorphism is localized within a probable binding site for Sp1, a ubiquitous transcription factor common in TATA-less genes such as PON1 [3].…”
Section: Discussionsupporting
confidence: 84%
“…Adipokine imbalance leads to an increase of inflammatory mediators, which, in turn, will trigger the proatherogenic and proinflammatory activities of the HDL-PON1 complex (24). Similar to other cross-sectional studies (25), multiple regression analysis showed that the Q192R polymorphism is the major determinant of P-ase, while L55M polymorphism influenced all three activities.…”
Section: Discussionsupporting
confidence: 73%
“…They found that PON1–192, PON1-107 and PON1–55 genotype, alcohol consumption, smoking and HDL levels are determinants of serum PON1 phenotype. They concluded that the contributions of the genetic markers to the PON1 phenotype are stronger than the contributions of the lifestyle determinants [27]. In this study the reference population did not consist of exclusively healthy individuals.…”
Section: Discussionmentioning
confidence: 97%
“…Phenotype is also influenced by environmental factors. Recently, Roest et al [27] investigated the determinants of PON1 bioavailability and activity in postmenopausal women. They found that PON1–192, PON1-107 and PON1–55 genotype, alcohol consumption, smoking and HDL levels are determinants of serum PON1 phenotype.…”
Section: Discussionmentioning
confidence: 99%